Why 'A forest conscienceness'? - Calver, M.; Bigler-Cole, H.; Bolton, G.; Dargavel, J.; Gaynor, A.; Horwitz, P.; Mills, J.; Wardell-Johnson, Grant (Millpress, 2005)
The phrase 'a forest conscienceness' was used in a major statement made by Charles Lane Poole, Western Australia's Conservator of Forests from 1916-1921, for the 1920 British Empire Forestry Conference. It is both relevant and contemporary at the beginning of the 21st century. We chose it as the conference theme to encourage engagement with both a conscious awareness of forests and their values, and a sense of moral responsibility toward forest management. It stimulated a broad range of lively contributions that emphasized mainly the 'awareness' aspect, although some authors addressed 'moral responsibility'. Perhaps 'conscienceness', like sustainability, is an evolving concept not yet fully mature. It warrants further engagement.